Pharmacological studies into cyclo-oxygenase, lipoxygenase and phospholipase in smooth muscle contraction in the isolated trachea. - Mitchell, H. W. (Nature Publishing Group, 1984)
Indomethacin (1 microM) enhanced histamine-induced contractions in pig and guinea-pig isolated tracheae. Mepacrine (30-50 microM) abolished this effect of indomethacin suggesting that contractile metabolites of arachidonate are involved in the response to indomethacin. Mepacrine (100 microM) in the absence of indomethacin also markedly reduced histamine-induced contractions (81.2% inhibition) in the pig trachea, without affecting responses to acetylcholine. Histamine-induced responses in the guinea-pig trachea were similarly reduced, but with a higher concentration of mepacrine (300 microM). BW755c (226 microM) enhanced histamine-induced contractions in some pig tracheal preparations and caused inhibition in others. These effects of BW755c were negatively correlated to the initial reactivity of the muscle to histamine such that weak contractions were potentiated and strong contractions were inhibited. A similar effect was seen with phenidone (100 microM). The results with BW755c and phenidone suggest that muscle reactivity (to histamine) may be partly determined by the balance between the release of inhibitory and contractile arachidonate metabolites. Mepacrine exerts a different effect indicating that histamine-induced contractions are regulated by a mepacrine-sensitive process which appears to be separate from the metabolism of arachidonate.